Effect of low temperature, low water vapor pressure environments on the fatigue behavior of an Al-Li aerospace alloy. (July 2021) - Brown, Luke B.; Jones, Jennifer L.; (Warner) Locke, Jenifer S.; Burns, James T.
Highlights: The effects of low water vapor, low temperature environments, on the FCGR of 2199 AA. FCGR was found to decrease with decreasing water vapor pressure systematically. Temperature was varied from 23C to −65 °C and only −30 °C and −50 °C effected FCGR. The proposed reasoning for low temp changes in FCGR are H-dislocation interactions. Abstract: The objective of the study is to evaluate the fatigue crack growth of a third-generation Al-Li-Cu alloy (2199-T86) in environments relevant to high-altitude flight. Reduction of PH2O at 23 °C resulted in a general reduction of crack growth rates. A local minimum in growth rates were observed at intermediate ΔK and PH2O and was attributed to roughness induced impedance of water transport through the crack wake. Decreasing temperature had no effect on growth kinetics down to −15 °C, but decreased crack rates were observed at −30 °C and −50 °C.